Analisis Tingkat Kepuasan Pelanggan Dalam Membeli Peralatan Kue Dengan Menggunakan Metode Rough Set Pada PT. XYZ - Silvia Lestari (Yayasan Literasi Sains Indonesia, 2022)
The level of customer satisfaction is very important for every company that carries out its business activities by selling the goods it produces. A company usually does a lot of activities to attract market prey to attract customers to buy its products, therefore paying attention to customer satisfaction is very important to know how the company's image among customers and among people who use the products of a company. making companies work harder in providing services, especially in controlling the feasibility of their products to satisfy customers. Cake equipment or cake ingredients are growing rapidly at this time, therefore researchers are trying to help the company in knowing the level of customer satisfaction using one of the existing methods. in the field of data mining, namely the Rough Set method. This method is expected to be effective in measuring the level of customer satisfaction and where later from the results to be obtained the company will know more about the level of customer satisfaction and the provision of menstruation for customers. for customers with different satisfaction criteria.